Link and Match Policy Implementation through Field Work Practice in Vocational Education: A Van Meter and Van Horn Analysis at SMK Al Amanah, Bandung Regency - Agung Wibawa; Faizal Madya; Vivi Indra Amelia Nasution (Dinasti Research, 2026)
This study examines the implementation of the Link and Match Program between the education and industrial sectors through Field Work Practice (Praktik Kerja Lapangan/PKL) at SMK Al Amanah, Bandung Regency. It is grounded in the gap between the goals of vocational education and actual conditions, since the labor force in Bandung Regency remains dominated by senior high school graduates, while the employment absorption rate of SMK Al Amanah graduates in the 2024–2025 academic year reached less than half of total graduates. The object of the research is the implementation of the Link and Match policy through PKL at SMK Al Amanah. This research aims to describe the implementation of the program and identify the obstacles faced by the school in carrying it out. The study employed a qualitative approach with a descriptive-analytical method, with informants selected through purposive sampling, including the principal, vice principal, PKL supervising teachers, industry partner representatives, and students. Data were collected through in-depth interviews and participatory observation, analyzed using an interactive model of data reduction, display, and conclusion drawing, with validity examined through triangulation. The analysis was guided by Van Meter and Van Horn's policy implementation theory. Findings indicate that the policy implementation has been running but is not yet optimal, marked by a low graduate absorption rate, limited practical facilities, and insufficiently effective communication between the school and industry partners. The study concludes that the program's success requires strengthening human resources, improving learning facilities, and fostering sustainable cooperation between the school and the industrial world.